New Method of Optimal Design of Electrical Rotating Machines - Flur Ismagilov; Vyacheslav Vavilov; Valentina Ayguzina; Vladimir Bekuzin (Institute of Advanced Engineering and Science, 2017)
The article presents a new method of the optimal design of the electrical rotating machine based on genetic algorithm. The mathematical description of the proposed algorithm is developed, and the optimal design of the high-speed electrical rotating machine by proposed method is performed. A new method for optimal design allows obtaining a new electrical rotating machine which mass is lower than mass of the initial electrical rotating machine by two times; the value of the rotor active length is lower by 2.37 times and the current density is higher by 1.7 times in comparison with the initial electrical rotating machine. The losses are increased by only 25 percent (power, rotation frequency and materials of both electrical rotating machine are the same).